Insight into the Functional Role of SiMPK6 in Stress Response and Photosynthetic Efficiency in Setaria italica - Dan Zhu; Xiaobing Hu; Hailong Wang; Yonghu Zhang; Xianglong Li; Wenqing Song; Rui Wen; Feng Feng; Ran Chai; Jianhua Wei; Jiewei Zhang (Plants)
Foxtail millet (Setaria italica), a significant C4 model crop known for its exceptional photosynthetic efficiency and robust environmental adaptability, serves as an excellent model for investigating C4 photosynthesis and crop stress resilience. When subjected to abiotic stress, foxtail millet employs a sophisticated signal transduction network to regulate its physiological processes, ensuring sustained high photosynthetic efficiency and normal growth. The mitogen-activated protein kinase (MAPK) family plays a key role in plant growth, development, and stress response. Here, we identified and named a MAPK in S. italica as SiMPK6. Fluorescence quantitative PCR analysis revealed that SiMPK6 is mainly expressed in the leaves during the early shooting stage, with induction under various abiotic stresses such as low temperature, high osmotic pressure, high salt, high temperature, and high light. Overexpressing the SiMPK6 in Arabidopsis thaliana mitigated damage to photosystem II induced by stress, underscoring the gene’s crucial role in foxtail millet’s stress signal transduction and maintenance of high photosynthetic efficiency.